Rational Use of Medicine in the Treatment of Helminth Infection : A Mini Review - Trasia, Reqgi First (Talenta Publisher, 2021)
Indonesia still has health problem, especially soil transmitted helminth. These helminths can cause deteriorate health, nutrition, intelligence and productivity of patients so causes a lot of losses economically. The aim of this article is to review the rational treatment of helminth infection. Albendazole, mebendazole, and pyrantel pamoate are the drugs recommended by the WHO. However, the uses of the three are different, especially for mass treatment or selective medicine. This review conclude that the three drugs are used according to the target patient's age with dosages and preparations that must be adjusted.